Sensitivity of ENSO Simulation to the Convection Schemes in the NESM3 Climate System Model: Atmospheric Processes - Ma, Libin; Jiang, Zijun (Frontiers in Earth Science, 2021)
The El Niño-Southern Oscillation (ENSO) is the most prominent climate system in the tropical Pacific. However, its simulation, including the amplitude, phase locking, and asymmetry of its two phases, is not well reproduced by the current climate system models. In this study, the sensitivity of the ENSO simulation to the convection schemes is discussed using the Nanjing University of Information Science and Technology Earth System version 3.0 (NESM3) model. Three convection schemes, including the default, the default coupled with the stochastic multicloud model (SMCM), and the default used in the Coupled Model Intercomparison Project Phase 6 (CMIP6), are implemented. The model results reveal that the low-level cloud cover and surface net shortwave radiation are best represented over the tropical Pacific in the model containing the SMCM. The simulations of the ENSO behavior’s response to changes in the convection scheme are not uniform. The model results reveal that the model containing the SMCM performs best in terms of simulating the seasonal cycle of the sea surface temperature anomaly along the equatorial Pacific, the phase locking, and the power spectrum of ENSO but with a modest ENSO amplitude. Compared to the model containing the default convection scheme, the coupling of the default scheme and the SMCM provides a good simulation of the ENSO’s asymmetry, while the model containing the CMIP6 convection scheme outperforms the others in terms of the simulation of the ENSO’s amplitude. Two atmospheric feedback processes were further discussed to investigate the factors controlling the ENSO’s amplitude. The analyses revealed that the strongest positive atmospheric Bjerknes feedback and the thermodynamic damping of the surface net heat flux occurred in the model containing the CMIP6 convection scheme, suggesting that the atmospheric Bjerknes feedback may overwhelm the heat flux damping feedback when determining the ENSO’s amplitude. The results of this study demonstrate that perfectly modeling and predicting the ENSO is not simple, and it is still a large challenge and issue for the entire model community in the future.